(untitled) (Research, Society and Development, 2021)
Insect pests are the main concern of farmers, this has led them to use inadequate control practices; causing an indiscriminated use of chemical pesticides which has resulted in the deterioration and disharmonization of the environment and human health. In recent years, biopesticides have been used as a healthy alternative for the control of pest insects whose biocidal action mechanisms motivated this review. In this article, 63 scientific research articles on entomopathogens were used from which 20 correspond to topics from a genetic approach (virulence genes), 23 articles detail the mechanisms of action by entomopathogenic fungi, 08 explain the mechanisms of action that exerts the bacterium Bacillus thuringiensis and 12 articles on characteristics of commercial microbial bioinsecticides. It can be concluded that fungi and bacteria are the most entomopathogenic microorganisms used in the formulation of biopesticides, being the species Metarhizium anisopliae, Beauveria bassiana and Bacillus thuringiensis the most used species. From this last, its biocidal effectiveness is based on the action of the Cry protein and of the first mentioned its effectiveness depends on the adhesion of the spore to the cuticle of the pest insect.